Numerical analysis of stability for mined-out area in multi-field coupling - Luo, Zhou-quan; Xie, Cheng-yu; Zhou, Ji-ming; Jia, Nan; Liu, Xiao-ming; Xu, Hai (Journal of Central South University, 2015)
There were differences between real boundary and blast hole controlling boundary of irregular mined-out area in underground metal mines. There were errors in numerical analysis of stability for goaf, if it was analyzed as regular 3D mined-out area and the influence of coupling stress-seepage-disturbance was not considered adequately. Taking a lead zinc mine as the background, the model was built by the coupling of Surpac and Midas-Gts based on the goaf model precisely measured by CMS. According to seepage stress fundamental equations based on the equivalent continuum mechanical and the theory about equivalent load of dynamic disturbance in deep-hole blasting, the stability of mined-out area under multi-field coupling of stress-seepage-dynamic disturbance was numerically analyzed. The results show that it is more consistent between the numerical analysis model based on the real model of irregular 3D shape goaf and the real situation, which could faithfully reappear the change rule of stress-strain about the surrounding rock under synthetic action of blasting dynamic loading and the seepage pressure. The mined-out area multi-field coupling formed by blasting excavation is stable. Based on combination of the advantages of the CMS, Surpac and Midas-Gts, and fully consideration of the effects of multi-field coupling, the accurate and effective way could be provided for numerical analysis of stability for mined-out area.